Changes in alveolar bone support induced by the Herbst appliance: a tomographic evaluation - João Paulo Schwartz; Taisa Boamorte Raveli; Humberto Osvaldo Schwartz-Filho; Dirceu Barnabé Raveli (Dental Press Editora, 2016)
ABSTRACT Objective: This study evaluated alveolar bone loss around mandibular incisors, induced by the Herbst appliance. Methods: The sample consisted of 23 patients (11 men, 12 women; mean age of 15.76 ± 1.75 years), Class II, Division 1 malocclusion, treated with the Herbst appliance. CBCT scans were obtained before treatment (T0) and after Herbst treatment (T1). Vertical alveolar bone level and alveolar bone thickness of mandibular incisors were assessed. Buccal (B), lingual (L) and total (T) bone thicknesses were assessed at crestal (1), midroot (2) and apical (3) levels of mandibular incisors. Student's t-test and Wilcoxon t-test were used to compare dependent samples in parametric and nonparametric cases, respectively. Pearson's and Spearman's rank correlation analyses were performed to determine the relationship of changes in alveolar bone thickness. Results were considered at a significance level of 5%. Results: Mandibular incisors showed no statistical significance for vertical alveolar bone level. Alveolar bone thickness of mandibular incisors significantly reduced after treatment at B1, B2, B3, T1 and significantly increased at L2. The magnitude of the statistically significant changes was less than 0.2 mm. The changes in alveolar bone thickness showed no statistical significance with incisor inclination degree. Conclusions: CBCT scans showed an association between the Herbst appliance and alveolar bone loss on the buccal surface of mandibular incisors; however, without clinical significance.